2021
DOI: 10.1016/j.omtn.2021.01.015
|View full text |Cite
|
Sign up to set email alerts
|

miR-130a activates the VEGFR2/STAT3/HIF1α axis to potentiate the vasoregenerative capacity of endothelial colony-forming cells in hypoxia

Abstract: Hypoxia modulates reparative angiogenesis, which is a tightly regulated pathophysiological process. MicroRNAs (miRNAs) are important regulators of gene expression in hypoxia and angiogenesis. However, we do not yet have a clear understanding of how hypoxia-induced miRNAs fine-tune vasoreparative processes. Here, we identify miR-130a as a mediator of the hypoxic response in human primary endothelial colony-forming cells (ECFCs), a well-characterized subtype of endothelial progenitors. Under hypoxic conditions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
1
6
0
1
Order By: Relevance
“…PB-ECFC EVs enriched with miR-10b-5p alleviate fibrosis by targeting the fibrotic genes Smurf1 and HDAC4 [ 59 ] PB-ECF-Cs MiRNA microarray PB-ECFC EVs ECFC EVs with miR-21-5p regulates autophagic flux to promote vascular endothelial repair by inhibiting SIPL1A2 in atherosclerosis [ 60 ] CB-EC-FCs MiRNA sequence CB-ECFC and ECFC EVs In vivo and in vitro, CB-ECFC EVs promote angiogenesis during ischaemic retinopathy The top five miRNAs enriched in CB-ECFC EVs compared to CB-ECFCs were miR-4532-5p, miR-451a-5p, miR-7704-5p, miR-486–2-5p, and miR-486–1-5p [ 61 ] CB-EC-FCs RNA sequence hypoxia GSE142123 Hypoxia impairs the initial outgrowth of CB-ECFCs and reduces the proliferation of cultured PB-ECFCs Gene expression profiles of PB-ECFCs under hypoxia show the regulation of the cell cycle and metabolism as major altered gene clusters [ 63 ] CB-EC-FCs Microarray CB-ECFC-s under normoxic oxygen and hypoxic conditions The DEGs of CB-ECFCs under hypoxic conditions are involved in cell apoptosis, cell cycle and MAPK pathways [ 64 ] CB-EC-FCs Microarray CB-ECFC-s under normoxic and hypoxic conditoins The PLAC8–NOX4 signalling axis improves the angiogenic functions of CB-ECFCs exposed to hypoxia [ 65 ] CB-EC-FCs RNA sequence ECFCs under normoxic and hypoxic conditions GSE142123 ANGPTL14, ENO2, ETXNIP, and SLC2A3 were upregulated while VEGFR2, NOS3, and FLT1 were downregulated. Although the HIF1 pathway is activated, there is no significant enrichment for the VEGFA pathway [ 66 ] CB-EC-FCs …”
Section: Transcriptome Analysismentioning
confidence: 99%
“…PB-ECFC EVs enriched with miR-10b-5p alleviate fibrosis by targeting the fibrotic genes Smurf1 and HDAC4 [ 59 ] PB-ECF-Cs MiRNA microarray PB-ECFC EVs ECFC EVs with miR-21-5p regulates autophagic flux to promote vascular endothelial repair by inhibiting SIPL1A2 in atherosclerosis [ 60 ] CB-EC-FCs MiRNA sequence CB-ECFC and ECFC EVs In vivo and in vitro, CB-ECFC EVs promote angiogenesis during ischaemic retinopathy The top five miRNAs enriched in CB-ECFC EVs compared to CB-ECFCs were miR-4532-5p, miR-451a-5p, miR-7704-5p, miR-486–2-5p, and miR-486–1-5p [ 61 ] CB-EC-FCs RNA sequence hypoxia GSE142123 Hypoxia impairs the initial outgrowth of CB-ECFCs and reduces the proliferation of cultured PB-ECFCs Gene expression profiles of PB-ECFCs under hypoxia show the regulation of the cell cycle and metabolism as major altered gene clusters [ 63 ] CB-EC-FCs Microarray CB-ECFC-s under normoxic oxygen and hypoxic conditions The DEGs of CB-ECFCs under hypoxic conditions are involved in cell apoptosis, cell cycle and MAPK pathways [ 64 ] CB-EC-FCs Microarray CB-ECFC-s under normoxic and hypoxic conditoins The PLAC8–NOX4 signalling axis improves the angiogenic functions of CB-ECFCs exposed to hypoxia [ 65 ] CB-EC-FCs RNA sequence ECFCs under normoxic and hypoxic conditions GSE142123 ANGPTL14, ENO2, ETXNIP, and SLC2A3 were upregulated while VEGFR2, NOS3, and FLT1 were downregulated. Although the HIF1 pathway is activated, there is no significant enrichment for the VEGFA pathway [ 66 ] CB-EC-FCs …”
Section: Transcriptome Analysismentioning
confidence: 99%
“…Previous reviews have presented summaries of the roles played by miRNAs in regulating EPC proliferation, mobilization, migration, differentiation, apoptosis, autophagy, senescence, adhesion, and tubule formation, as well as EPC-induced angiogenesis ( 51 ). EPCs face the challenge of hypoxia in ischemic tissue, and overexpression of miR-130a and miR-210-3p at the cellular level can enhance the proliferation, migration and tube formation of EPCs under hypoxic conditions ( 34 , 35 ). Li et al found that EPCs transfected with miR-326-5p exhibited significantly increased tube formation in Matrigel plugs and angiogenesis in the MI model ( 36 ).…”
Section: Epc Recruitment Is Regulated By Non-coding Rnasmentioning
confidence: 99%
“…Interestingly, VEGF-A pathway activation in EPCs during hypoxia, while increases in related proteins were detected from NOS pathway, inositol and calcium signaling, G protein signaling, inflammation, and phospholipase signaling ( 68 ). In addition, VEGF has been shown to bind to VEGFR2 and activate the PI3K/Akt/eNOS ( 69 ), ERK1/2 ( 70 , 71 ), and STAT3 pathways ( 34 , 72 ). The VEGF signaling pathway in EPCs plays important potential roles in the regulation of redox homeostasis, cell survival, cell migration, angiogenesis, and vascular regeneration ( 68 ).…”
Section: Epc Recruitment-related Signaling Pathwaysmentioning
confidence: 99%
“…La tubulogénesis de las CE, también se ve facilitada por la expresión de miR-210 asociada con la hipoxia [34]. Curiosamente, en condiciones de normoxia, la sobreexpresión de miR-130a no provoca tales efectos [35].…”
Section: Hipoxiaunclassified